Salt induces features of a dormancy-like state in seeds of Eutrema (Thellungiella) salsugineum, a halophytic relative of Arabidopsis - Kazachkova, Yana; Khan, Asif; Acuña, Tania; López-Díaz, Isabel; Carrera, Esther; Khozin-Goldberg, Inna; Fait, Aaron; Barak, Simon (Frontiers in plant science, 2016)
The salinization of land is a major factor limiting crop production worldwide. Halophytes adapted to high levels of salinity are likely to possess useful genes for improving crop tolerance to salt stress, as well as providing a food source on marginal lands. However, despite being salt-tolerant plants, the seeds of many halophytes will not germinate on saline soils, yet little is understood regarding biochemical and gene expression changes underlying salt-mediated inhibition of halophyte seed germination. We have used the halophytic Arabidopsis relative model system, Eutrema (Thellungiella) salsugineum to explore salt-mediated inhibition of germination. We show that E. salsugineum seed germination is inhibited by salt to a far greater extent than in Arabidopsis, and that this inhibition is in response to the osmotic component of salt exposure. E. salsugineum seeds remain viable even when germination is completely inhibited, and germination resumes once seeds are transferred to non-saline conditions. Moreover, removal of the seed coat from salt-treated seeds allows embryos to germinate on salt-containing medium. Mobilization of seed storage reserves is restricted in salt-treated seeds, while many germination-associated metabolic changes are arrested or progress to a lower extent. Salt-exposed seeds are further characterized by a reduced GA/ABA ratio and increased expression of the germination repressor genes, RGL2, ABI5 and DOG1. Furthermore, a salt-mediated increase in expression of a LATE EMBRYOGENESIS ABUNDANT gene and accretion of metabolites involved in osmoprotection indicates induction of processes associated with stress tolerance, and accumulation of easily mobilized carbon reserves. Overall, our results suggest that salt inhibits E. salsugineum seed germination by inducing a seed state with molecular features of dormancy while a physical constraint to radicle emergence is provided by the seed coat layers. This seed state could facilitate survival on saline soils until a rain event(s) increases soil water potential indicating favorable conditions for seed germination and establishment of salt-tolerant E. salsugineum seedlings.
Gesehen am 07.05.2020